The Effect of Formula and Cooking Temperature on Sereal Characteristics of Purple Sweet Potato and Corn Composite Flour: Pengaruh Formula dan Suhu Pemasakan terhadap Karakteristik Sereal dari Tepung Komposit Ubi Jalar Ungu dan Jagung - Rafdi , M Hafizh; Supriyanto, Supriyanto; Hidayati, Darimiyya (JITIPARI (Jurnal Ilmiah Teknologi dan Industri Pangan UNISRI), 2024)
The cereal products available in the market mostly focus only on practicality and ignore the nutritional content. It is necessary to increase the nutritional content of these products by using local Indonesian raw materials such as sweet potatoes and corn.  The objectives of this study are: 1) to determine the effect of temperature and proportion of purple sweet potato flour and corn flour on the characteristics of cereals produced, 2) to assess the level of preference of panelists for the physical, chemical and sensory qualities of cereals produced. The study design used a factorial randomized design complete with a proportion treatment of purple sweet potato flour and corn. Test parameters include water content, degree of swelling, water absorption, texture, antioxidants, and sensory evaluation. The conclusion in this study is that the comparative treatment of purple sweet potato flour and corn and temperature did not have a real effect on water content, degree of development, water absorption index (IPA), water solubility index (IKA), texture and antioxidants but had an effect on sensory properties